2011
DOI: 10.1177/0748233711420473
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of zinc oxide nanoparticles through oral route

Abstract: This experiment was aimed to determine the significance of dose by comparing acute oral toxicological potential of nano-sized zinc oxide (20 nm) with its micro-sized zinc oxide. Sprague Dawley rats, 8 to 9 weeks old, were administered with 5, 50, 300, 1000 and 2000 mg/kg body weight (b.w.) of nano- and micro-sized zinc oxide suspended in distilled water once through oral gavage. The effects of the micro- and nano-sized zinc oxide on biochemical and hematological parameters were analyzed on day 14 of administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 22 publications
2
75
2
1
Order By: Relevance
“…In liver tissue, the hydropic degeneration around the central vein was prominent and the spotty necrosis of hepatocyte was also found in the female mice postexposure 2 weeks to the 80 nm and fine TiO 2 particles. Pasupuleti et al [28] showed that the Liver with nanozinc oxide at dose of 2000 mg/kg B.W. appears focal necrosis of liver.…”
Section: Hematology Findings Of Current Study Inmentioning
confidence: 99%
“…In liver tissue, the hydropic degeneration around the central vein was prominent and the spotty necrosis of hepatocyte was also found in the female mice postexposure 2 weeks to the 80 nm and fine TiO 2 particles. Pasupuleti et al [28] showed that the Liver with nanozinc oxide at dose of 2000 mg/kg B.W. appears focal necrosis of liver.…”
Section: Hematology Findings Of Current Study Inmentioning
confidence: 99%
“…Several rodent feeding studies have demonstrated particle sizedependent effects on the intestinal uptake of ZnO nanoparticles, with a smaller particle size leading to a higher uptake. [40][41][42][43] One study reported that a single oral dose of ZnO nanoparticles caused hepatic injury, kidney toxicity, and lung damage. 44 Interestingly, one study showed that ZnO nanoparticles were not toxic when used in isolation, but that they become toxic when mixed with ascorbic acid.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…[8][9][10] Several studies have begun to investigate the toxicity of inorganic nanoparticles to intestinal epithelial cells both in vitro 9 and in vivo. [11][12][13][14] Based on the toxicity studies that have been conducted in different systems, it is apparent that toxicity depends upon many different properties of nanoparticles. Particle size influences toxicity, with nanoparticles showing greater toxicity than their larger counterparts.…”
Section: Introductionmentioning
confidence: 99%